2010
DOI: 10.1590/s1808-18512010000400010
|View full text |Cite
|
Sign up to set email alerts
|

Correlação entre as classificações de Pfirrmann e Modic na degeneração do disco intervertebral lombar

Abstract: OBJETIVO: correlacionar as alterações encontradas nas ressonâncias magnéticas lombares quanto às classificações de Pfirrmann e Modic. MÉTODOS: foram selecionadas 54 ressonâncias lombossacras de pacientes ambulatoriais (23 homens e 31 mulheres) que já se encontravam em investigação por sua comorbidade. Foram classificados 264 discos intervertebrais (L1 a S1) quanto ao grau de degeneração segundo Pfirrmann. A presença de alterações de sinal de corpo vertebral foi registrada quanto à classificação de Modic. Foi a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
2
2
0
3
Order By: Relevance
“…20 In the study, most patients did not present Modic type changes (88.7%). In accordance with the findings of Leite et al (88.3%) 21 , no Modic type 3 changes were observed, a situation that is uncommon. 9,22,23 Previous studies demonstrated similar relationships in terms of the frequency and location of Modic changes in the intervertebral discs studied.…”
Section: Discussionsupporting
confidence: 92%
“…20 In the study, most patients did not present Modic type changes (88.7%). In accordance with the findings of Leite et al (88.3%) 21 , no Modic type 3 changes were observed, a situation that is uncommon. 9,22,23 Previous studies demonstrated similar relationships in terms of the frequency and location of Modic changes in the intervertebral discs studied.…”
Section: Discussionsupporting
confidence: 92%
“…Most of the sample (87%) had a Pfirrmann-max ≥ 3, which demonstrates that a large portion had at least one disc with moderate or marked degeneration. This finding is partially in accordance with those of previous publications that found signs of significant disc degeneration in 55.2% to 84.5% 22 23 24 of the patients, although we found 22.5% of discs without degeneration in the L5-S1 segment. This data demonstrates a characteristic of our sample, which may be related to the predominant age group (71.25% of patients aged between 41 and 60 years); in samples of the same age group, other authors found similar results.…”
Section: Discussionsupporting
confidence: 94%
“…This data demonstrates a characteristic of our sample, which may be related to the predominant age group (71.25% of patients aged between 41 and 60 years); in samples of the same age group, other authors found similar results. 25 According to other studies, 22 23 25 disc degeneration is more prevalent and accentuated in low lumbar levels, from L3-L4 to L5-S1, being more frequent and accentuated in L4-L5.…”
Section: Discussionmentioning
confidence: 90%
“…Nosso estudo apresentou uma frequência de 85,8% dos discos doentes. Leite et al 19 observaram uma frequência menor, provavelmente pela inclusão dos níveis L1-L2 e L2-L3 e pela menor média de idade dos pacientes avaliados.…”
Section: Discussionunclassified